2021
DOI: 10.3390/ijms22031172
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic and Cold Atmospheric Plasma Combination Therapy Using Polymeric Nanoparticles for the Synergistic Treatment of Cervical Cancer

Abstract: Integrating multi-modal therapies into one platform could show great promise in overcoming the drawbacks of conventional single-modal therapy and achieving improved therapeutic efficacy in cancer. In this study, we prepared pheophorbide a (Pheo a)/targeting ligand (epitope analog of oncoprotein E7, EAE7)-conjugated poly(γ-glutamic acid) (γ-PGA)/poly(lactide-co-glycolide)-block-poly(ethylene glycol) methyl ether (MPEG-PLGA)/hyaluronic acid (PPHE) polymeric nanoparticles via self-assembly and encapsulation metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…In vitro studies have been conducted on a wide range of gynaecological cell lines (see also Table 1 in the work of Zubor et al [ 68 ]) of cervical cancer [ 69 , 70 , 71 , 72 ], ovarian cancer [ 73 , 74 , 75 , 76 , 77 , 78 ], and colon cancer [ 79 , 80 , 81 ], see Table 3 . With an aim to increase differences in cell response between healthy and cancer cells, more intricate applications are in development, combining CAP with hyperthermia [ 82 ], radiotherapy [ 72 ], or photodynamic therapy using targeted polymeric nanoparticles [ 83 ].…”
Section: Resultsmentioning
confidence: 99%
“…In vitro studies have been conducted on a wide range of gynaecological cell lines (see also Table 1 in the work of Zubor et al [ 68 ]) of cervical cancer [ 69 , 70 , 71 , 72 ], ovarian cancer [ 73 , 74 , 75 , 76 , 77 , 78 ], and colon cancer [ 79 , 80 , 81 ], see Table 3 . With an aim to increase differences in cell response between healthy and cancer cells, more intricate applications are in development, combining CAP with hyperthermia [ 82 ], radiotherapy [ 72 ], or photodynamic therapy using targeted polymeric nanoparticles [ 83 ].…”
Section: Resultsmentioning
confidence: 99%
“…In our pilot study, CAP was used as a monotherapy. However, different studies have revealed a great potential of CAP as a combination partner with other, in particular Hofmeyer/Weber/Gerds/Emmert/Thiem oncological, treatments [62][63][64]. In rosacea, using CAP in conjunction with other treatments might also be advantageous due to different aspects: On the one hand, CAP combination with topical drugs might increase their efficacy due to its enhancement of stratum corneum permeabilization [65,66].…”
Section: Discussionmentioning
confidence: 99%
“…Photosensitizers are indispensable for PDT. Under light conditions, photosensitizer molecules in the excited state interact with substances such as oxygen and water molecules inside tissues to form free radicals, which contribute to cancer cell damage and apoptosis by elevating intracellular oxidative stress levels ( 32 ). However, electrons in the excited state in photosensitizers are usually unstable and prone to be trapped by electron holes in molecules inside or outside and reattributed to the ground state, thus disfavoring the formation of free radicals ( 33 ).…”
Section: Discussionmentioning
confidence: 99%